2020
DOI: 10.1111/ijcs.12598
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic motivators of collaborative consumption: A study of accommodation rental services

Abstract: The transition from linear to circular economy requires increasing and promoting sustainable production and consumption models based on reducing, reusing and sharing of resources. Together with access-based services and using secondhand products, collaborative consumption (CC) is one of the crucial tools of sustainable consumption (Edbring, Lehner, & Mont, 2016). CC is an alternative consumption model to reduce the use of resources by sharing, swapping or bartering the goods and services (Botsman & Rogers, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Economic incentives attract the low‐ and mid‐income population segment (Schaefers et al, 2018; Tussyadiah & Pesonen, 2018). Individuals possessing personality characteristics like intelligence, openness to experience, extraversion, conscientiousness, agreeableness and cosmopolitanism are more likely to adopt shared consumption (Aspara & Wittkowski, 2019; Juric et al, 2021; Tunçel & Tektaş, 2020). Further, individuals' pro‐attitude towards technology, the environment and de‐ownership induce sharing intention (Acheampong & Siiba, 2020; Lindblom & Lindblom, 2017).…”
Section: Thematic Content Analysis and Synthesismentioning
confidence: 99%
“…Economic incentives attract the low‐ and mid‐income population segment (Schaefers et al, 2018; Tussyadiah & Pesonen, 2018). Individuals possessing personality characteristics like intelligence, openness to experience, extraversion, conscientiousness, agreeableness and cosmopolitanism are more likely to adopt shared consumption (Aspara & Wittkowski, 2019; Juric et al, 2021; Tunçel & Tektaş, 2020). Further, individuals' pro‐attitude towards technology, the environment and de‐ownership induce sharing intention (Acheampong & Siiba, 2020; Lindblom & Lindblom, 2017).…”
Section: Thematic Content Analysis and Synthesismentioning
confidence: 99%
“…Studies on the intention of rental consumption observed that "financial cost" is one of the prime motivators for consumers to opt for the same (Park & Armstrong, 2019). Besides, the literature showed that people try renting their homes because they are open to new experiences (Pantano & Stylos, 2020;Tunçel & Özkan Tektas ¸, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research (cf. Tunçel and Özkan Tektaş, 2020) has related the sharing economy with collaborative consumption and peer-to-peer markets. Here, sharing economy is considered an economic model that is based on traditional sharing, bartering, lending, trading, renting, gifting and swapping, but redefined through new digital technologies and peer communities.…”
Section: Literature Reviewmentioning
confidence: 99%